Home quarantine during COVID-19 blunted childhood trauma-related psychiatric symptoms in Chinese college students - Wenjuan Hong; Qiang Wang; Qinghong Hou; Nan Zhao; Ruoling Wang; Yan Bai; Chengping Hu; Weiqing Liu (Frontiers Media S.A., 2023)
BackgroundChildhood trauma confers risks to mental health. However, little is known about whether home quarantine (HQ) during the coronavirus disease 2019 (COVID-19) pandemic exaggerated or mitigated the effect of childhood trauma on mental health.ObjectiveTo examine the modulating effects of prior childhood traumas on the longitudinal changes of psychiatric symptoms in college students before and after HQ during the pandemic.MethodsThis was a two-wave longitudinal study on the mental health of 2,887 college students before and after HQ during the COVID-19 pandemic. The relationships between the changes in the Patient Health Questionnaire-9 (PHQ-9), Symptom Checklist-90 (SCL-90), 16-item Prodromal Questionnaire (PQ-16), Childhood Trauma Questionnaire (CTQ), and Social Support Rating Scale (SSRS) scores were analyzed.ResultsThe students with childhood trauma showed a significantly greater decrement in psychiatric symptoms after HQ (F = 17.21, 14.11, 18.87, and 17.42 for PHQ-9, PQ-16 objective and distress, and SCL-90, respectively). The correlation coefficients between the CTQ and these symptoms scales were significant at baseline (r = 0.42, 0.34, 0.37, and 0.39), and decreased after HQ (r = 0.17, 0.20, 0.18, and 0.19). The decrement of depressive, psychotic, and overall symptoms was positively correlated with the scores of the CTQ (r = 0.08-0.27) but negatively correlated with SSRS (r = −0.08−−0.14). Multilinear regression analysis confirmed the results of the CTQ and SSRS regarding the modulation of the dynamic changes in psychiatric symptoms. A constructed structural equation model indicated that the total effects of childhood trauma on decreased psychiatric symptoms were partly mediated by lower baseline social support.ConclusionHome quarantine during the COVID-19 pandemic could blunt the adverse effects of childhood trauma on mental health, especially for prodromal psychotic symptoms in college students. Changes in relative deprivation and social support may be mediating factors.